1999
DOI: 10.1074/jbc.274.40.28771
|View full text |Cite
|
Sign up to set email alerts
|

Selective Loss of either the Epimerase or Kinase Activity of UDP-N-acetylglucosamine 2-Epimerase/N-Acetylmannosamine Kinase due to Site-directed Mutagenesis Based on Sequence Alignments

Abstract: N-Acetylneuraminic acid is the most common naturally occurring sialic acid, as well as being the biosynthetic precursor of this group of compounds. UDP-GlcNAc 2-epimerase/N-acetylmannosamine kinase has been shown to be the key enzyme of N-acetylneuraminic acid biosynthesis in rat liver, and it is a regulator of cell surface sialylation. The N-terminal region of this bifunctional enzyme displays sequence similarities with prokaryotic UDP-GlcNAc 2-epimerases, whereas the sequence of its C-terminal region is simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
136
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 112 publications
(144 citation statements)
references
References 33 publications
5
136
1
2
Order By: Relevance
“…ManNAc kinase activity was retained in the N-terminal mutants C13S, H132Q, D176V, D177C, V331A, and D378Y, whereas the C-terminal mutants I472T, V572L, A630T, A631V, and G703S showed dramatic reductions in activities. These data were essentially compatible with a prior report (13). Interestingly, the A524V mutant preferentially affected UDP-GlcNAc 2-epimerase activity, although the mutation is in the kinase domain.…”
Section: Novel Mutations In Gne Gene In Dmrv Patients-supporting
confidence: 82%
See 4 more Smart Citations
“…ManNAc kinase activity was retained in the N-terminal mutants C13S, H132Q, D176V, D177C, V331A, and D378Y, whereas the C-terminal mutants I472T, V572L, A630T, A631V, and G703S showed dramatic reductions in activities. These data were essentially compatible with a prior report (13). Interestingly, the A524V mutant preferentially affected UDP-GlcNAc 2-epimerase activity, although the mutation is in the kinase domain.…”
Section: Novel Mutations In Gne Gene In Dmrv Patients-supporting
confidence: 82%
“…Enzymatic Activities of GNE Mutants in DMRV PatientsSite-directed mutagenesis of the GNE protein has shown that the two enzymatic activities are separately and independently catalyzed by two domains, an N-terminal epimerase domain and a C-terminal kinase domain (13). Previously, we reported reductions in UDP-GlcNAc 2-epimerase activities in leukocytes from the patients with mutations in the GNE gene (8).…”
Section: Novel Mutations In Gne Gene In Dmrv Patients-mentioning
confidence: 99%
See 3 more Smart Citations